From Bright Plots to Blind Spots: Mapping Departures in Case Review Post-Bail Reform in Two New Jersey Courts. (January 2021) - Rengifo, Andres F.; Flores, Sofía G.; Jackson, Ashley N.
This study documents the extent to which prosecutors and judges in New Jersey deviate from new case review protocols post-bail reform. We draw on a random sample of hearings observed in two courts ( N = 372) to (a) map prosecutorial requests to depart from risk-based recommendations for pretrial monitoring and (b) explore patterns in judicial review signaling more limited case processing. Findings show that in 16% of cases, prosecutors deviated from guidelines and most of these motions were adopted by judges to increase supervision. Deviations from process by judges were more frequent, with 39% of cases observed linked to one or more markers of reduced review. Multivariate results suggest that case-level factors influenced the patterning of these departures in different ways, with older defendants and most Latinx defendants receiving a more limited assessment of their cases. We discuss findings in connection to literature on corrections reform and smart decarceration initiatives.